National music and the mundo al día collection: remarks on a controversy (2003)
Between 1924 and 1938 the newspaper Mundo al Día from Bogotá published the largest collection of printed sheet music (both in terms of quantity and distribution) ever achieved by a Colombian newspaper. The Mundo al Día Collection had a strong impact on the idea of the construction of a national cultural identity through music. Since its inception, the collection was linked to a controversy around national music that occupied center stage in the cultural debate during the 20's and 30's. Many articles regarding this topic were published in Mundo al Día. The object of this article is to point out the antecedents of the controversy, its development, its incidence on Mundo al Día 's ""Collection, and its transformation during the 30's, when the newspaper went out of print.